The long-term outcome of children with VP shunt and hydrocephalus: motor developmental outcome and QOL of patients with hydrocephalus is associated with the number of revisional procedures but is not impacted by the type of the valve - Wendling-Keim, Danielle S.; Luz, Hannah; Kren, Elena; Muensterer, Oliver; Lehner, Markus (Frontiers in Surgery, 2025)
PurposeDespite constant advances in ventriculo-peritoneal shunt systems, pediatric patients with hydrocephalus may present with neurodevelopmental delay. Therefore, we performed a study including a questionnaire, which aimed to analyze parameters that may have an impact on the cognitive function and quality of life of the pediatric patient with hydrocephalus.MethodsIn this retrospective study, we included 81 patients aged 0–17 with hydrocephalus who were treated with a ventriculo-peritoneal shunt at a single institution. Demographic data, etiology of the hydrocephalus, type of valve implanted, any revision procedures and any complications were analyzed and the neurodevelopmental outcome, epilepsy and quality of life were assessed using a questionnaire sent to these patients. Statistical analysis was performed using SPSS. The significance level was set at p ≤ 0.05.ResultsQuestionnaires were sent to 81 patients who were treated at our institution over a mean retrospective study period of 18 years. Of these, 30 questionnaires were completed by the patients themselves or with the support of their families and included in the study. The etiology of the hydrocephalus as a non-controllable parameter did not affect the cognitive and motor development as well as the occurrence of epilepsy, cephalalgia and the quality of life. However, the number of revisions had a significant (p = 0.041) impact on the motor development of the child. The mean Wellbeing Five score was better with 19.63 in the group with no revisions whereas the score was 12.2 in the group with more than two revisional procedures. The type of the valve (adjustable or not adjustable) as a controllable parameter did not change any of the tested parameters (p > 0.05).ConclusionThe number of revisional procedures significantly affected the motor development of pediatric patients with a ventriculo-peritoneal (VP) shunt calling for further research to improve VP shunt systems as well as surgical procedures like endoscopic third ventriculo-cisternostomy (ETV) in the future.